Reading tales aloud, a way to change the aggressiveness perception - Turriago Rincón, Liliana; González Herrera, Carolina; Peña Guerrero, Nelsy (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2017)
The present article is derived from a research developed to get the pedagogic magister degree from the Universidad de la Sabana, guided by the teacher Nelsy Peña Guerrero. This article presents some results that shows the incidence of an application of a didactic sequence with activities such as the reading aloud of tales, and the cooperative learning in the perception change of the students’ aggressiveness of level 503 of the school Distrital Carlos Albán Holguín sede A.